2022
DOI: 10.4081/jphr.2022.2144
|View full text |Cite
|
Sign up to set email alerts
|

Presence of <em>Leptospira</em> sp. and leptospirosis risk factor analysis in Boyolali district, Indonesia

Abstract: Background: Leptospirosis is a health problem that causes death in Indonesia. In 2017, Boyolali District was reported that the number of leptospirosis cases reached 40.62 per 100,000 population with a CFR of 23.52%. The determination of risk factors and Leptospira bacteria's presence in the body of water plays an essential role in the transmission of leptospirosis.Design and methods: This study aims to determine the risk factors and Leptospira bacteria's presence in water bodies in Boyolali District. This rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Skin that is eroded due to wounds or skin diseases makes it easier for Leptospira to enter the mucous membranes of the human body. The research results are in line with the research conducted by Setyaningsih et al (2022) in Boyolali District showed that a history of injury had a significant relationship with the incidence of Leptospirosis. This is evidenced by the results of statistical test studies showing an Odds Ratio value of 1.13 which means that people with a history of injuries have a 1.13 times greater chance of being exposed to Leptospirosis than people without a history of injuries.…”
Section: Discussionsupporting
confidence: 89%
“…Skin that is eroded due to wounds or skin diseases makes it easier for Leptospira to enter the mucous membranes of the human body. The research results are in line with the research conducted by Setyaningsih et al (2022) in Boyolali District showed that a history of injury had a significant relationship with the incidence of Leptospirosis. This is evidenced by the results of statistical test studies showing an Odds Ratio value of 1.13 which means that people with a history of injuries have a 1.13 times greater chance of being exposed to Leptospirosis than people without a history of injuries.…”
Section: Discussionsupporting
confidence: 89%
“…The results of this study show that there is a relationship between the variable presence of trash and the presence of mice positive for leptospira bacteria (ρ = 0.000). A study in Boyolali Regency conducted by Setyaningsih et al (2022) also stated that there is a significant relationship between the presence of waste and the incidence of Leptospirosis. This means that the presence of rubbish has a 2.13 times higher risk of transmitting leptospirosis (Setyaningsih et al, 2022).…”
Section: The Relationship Between the Presence Of Rubbish And Mice Th...mentioning
confidence: 97%
“…Leptospires were found in rivers (18.18%) wells (18.18%) and in rice fields (6.67%). Hence, cases occur almost every year in subdistricts [15]. Another report on leptospirosis from Semarang showed the median age of patients to be 41.2 years and 67% were male.…”
Section: Current Trend-epidemiologymentioning
confidence: 99%
“…At the hospital sites, leptospirosis was missed in 57% of cases but detected by the Reference Laboratory. Makassar and Surabaya (83.3%) and Yogyakarta (100%) had the highest missed case rates [4,15].…”
Section: Challenges In Diagnosis: Low Awareness Among the Population ...mentioning
confidence: 99%
See 1 more Smart Citation